2017
DOI: 10.1149/2.0491707jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of the Growth of Copper Nanowires in the Presence of Ethylenediamine through Mixed Potential

Abstract: Copper (Cu) nanowires about 90 nm in mean diameter and lengths of about 50 μm were successfully synthesized by electroless deposition at 60 • C in the presence of ethylenediamine (EDA). Without addition of EDA, only large Cu particles were formed in the solution. On the other hand, high quality nanowires were formed in the presence of 176 mM EDA. Below this amount, shorter Cu nanowires were observed. The mixed potential shifted to more negative values without EDA, indicating faster reduction rate. It is possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(136 reference statements)
0
13
0
Order By: Relevance
“…The main disadvantage of Cu nanowires is that, unlike Ag and Au, they are easily oxidized by atmospheric oxygen. Therefore, many research articles have been devoted to the synthesis of Cu nanowires, as well as coating methods to protect Cu nanowires from oxidation. Methods to make Cu nanowires include chemical vapor deposition, , electrochemical deposition in templates, , and solution-phase syntheses. Among these methods, solution-phase synthesis has the greatest potential for producing large quantities of nanowires at low cost . The solution-phase synthesis of Cu nanowires requires low reaction temperatures (60–100 °C) and can proceed at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main disadvantage of Cu nanowires is that, unlike Ag and Au, they are easily oxidized by atmospheric oxygen. Therefore, many research articles have been devoted to the synthesis of Cu nanowires, as well as coating methods to protect Cu nanowires from oxidation. Methods to make Cu nanowires include chemical vapor deposition, , electrochemical deposition in templates, , and solution-phase syntheses. Among these methods, solution-phase synthesis has the greatest potential for producing large quantities of nanowires at low cost . The solution-phase synthesis of Cu nanowires requires low reaction temperatures (60–100 °C) and can proceed at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The two main solution-phase syntheses for Cu nanowires involve the use of (1) ethylenediamine (EDA) in an alkaline (8–15 M NaOH) aqueous solution ,,,, and (2) alkylamines (e.g., hexadecylamine or octadecylamine) in a neutral aqueous solution. In the first synthesis, electrons from the oxidation of hydrazine (N 2 H 4 ) reduce tetrahydroxocuprate­(II) and dihydroxocuprate­(I) complexes while EDA promotes anisotropic growth by selectively inhibiting oxidation on the (111) facets at the end of a growing Cu nanowire . The dimensions of Cu nanowires can be controlled by changing the concentrations of NaOH, EDA, N 2 H 4 , reaction temperature, and stirring during the reaction. , For example, a decrease in the reaction temperature from 70 to 60 °C can increase the aspect ratio from 1860 to 5700, and a decrease in N 2 H 4 below 5.7 mM can decrease the diameter from 65 to 35 nm . Higher concentrations of EDA can reduce the nanowire aspect ratio and can also result in the formation of tapered Cu nanowires …”
Section: Introductionmentioning
confidence: 99%
“…Tan et al 80 demonstrated the necessity of using hydrazine to promote anisotropic reduction of Cu(II). Without EDA, only Cu particles are formed in the solution.…”
Section: Ethylenediamine (Eda)mentioning
confidence: 99%
“…The growth of CuNWs also was determined by the concentration of EDA. When EDA is injecting on the solution, CuNWs begin growth along the axial onedimensional (1-D) [13]. Fig.…”
Section: Fabrication Of Transparent Conducting Electrodementioning
confidence: 99%